ANALYSIS OF THE INFLUENCE OF TRANSFORMATIONAL GOVERNMENT LEADERSHIP ON COMMUNITY SATISFACTION IN DIGITAL PUBLIC SERVICES: A CASE STUDY OF E-SAMSAT - Saputri, Adelia; Yulyana, Eka (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study analyzes the influence of transformational government leadership on community satisfaction in digital public services through a case study of the e-Samsat application. The main problems identified are low levels of user participation and satisfaction due to lack of digital literacy, technical constraints, and negative perceptions of online bureaucracy. This study aims to evaluate the extent to which transformational leadership styles characterized by long-term vision, inspiration, and empowerment can improve service quality and public trust in digital public innovation. The methods used are literature studies and web observations on public responses and the latest news related to the implementation of e-Samsat in various Indonesian provinces, including reports from national media such as Kompas and Detik. The results show that transformational leadership, which actively encourages cross-sector collaboration and inclusive technology adaptation, contributes significantly to increased community satisfaction. The main success factors include information transparency, process efficiency, and two-way communication between the government and citizens. These findings underscore the importance of a progressive leadership approach in transforming digital-based public services.